A history of high-power laser research and development in the United Kingdom. (27th April 2021) - Danson, Colin N.; White, Malcolm; Barr, John R. M.; Bett, Thomas; Blyth, Peter; Bowley, David; Brenner, Ceri; Collins, Robert J.; Croxford, Neal; Dangor, A. E. Bucker; Devereux, Laurence; Dyer, Peter E.; et al.
Abstract: The first demonstration of laser action in ruby was made in 1960 by T. H. Maiman of Hughes Research Laboratories, USA. Many laboratories worldwide began the search for lasers using different materials, operating at different wavelengths. In the UK, academia, industry and the central laboratories took up the challenge from the earliest days to develop these systems for a broad range of applications. This historical review looks at the contribution the UK has made to the advancement of the technology, the development of systems and components and their exploitation over the last 60 years.